2019
DOI: 10.1371/journal.pone.0219423
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation and resorption markers at 7 years of age: Relations with growth and bone mineralization

Abstract: Purpose We aimed to describe bone formation and resorption markers in generally healthy prepubertal children using total alkaline phosphatase (tALP), osteocalcin (OC) and β-isomerized C-terminal telopeptides of type I collagen (β-CTx) serum concentrations and to estimate markers’ correlations with anthropometric growth (height, weight, body mass index and trajectories of weight gain) as well as bone mineral content (BMC) and areal density (aBMD). Methods We assessed 395… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…CTX exists in two forms: non-isomerized α-CTX and isomerized β-CTX. β-CTX is a marker of bone resorption ( Monjardino et al, 2019 ). Additionally, different pathways of collagen breakdown yield various fragments.…”
Section: Osteoporosis Evaluationmentioning
confidence: 99%
“…CTX exists in two forms: non-isomerized α-CTX and isomerized β-CTX. β-CTX is a marker of bone resorption ( Monjardino et al, 2019 ). Additionally, different pathways of collagen breakdown yield various fragments.…”
Section: Osteoporosis Evaluationmentioning
confidence: 99%
“…However, the association of these biomarkers with growth or bone mass in the human literature can be conflicting. For example, some studies have shown an association between bone biomarkers and height, but the biomarkers were not predictive of bone gain (bone mineral content and density) [ 53 , 54 ]. Conversely, other studies have shown that there are a number of determinants of serum biomarker concentration, including the sexual maturity rating (Tanner stage), sex, height, velocity, and whole-body bone mineral content [ 52 ].…”
Section: Overlaying Human Principles Of Growth With the Horsementioning
confidence: 99%
“…During childhood and adolescence, bone mass increases with age until it reaches its peak in young adulthood when skeletal development is mature. 2 …”
Section: Introductionmentioning
confidence: 99%